Towards a framework for knowledge discovery: an architecture for distributed inductive databases - Bruin, Jeroen S. de (2006)
We discuss how data mining, patternbases and databases can be integrated into inductive databases, which make data mining an inductive query process. We propose a software architecture for such inductive databases, and extend this architecture to support the clustering of inductive databases and to make them suitable for data mining on the grid.